2012
DOI: 10.7314/apjcp.2012.13.2.421
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Impact of Cancer in Member Countries of the Association of Southeast Asian Nations (ASEAN): the ACTION Study Protocol

Abstract: Cancer can be a major cause of poverty. This may be due either to the costs of treating and managing the illness as well as its impact upon people's ability to work. This is a concern that particularly affects countries that lack comprehensive social health insurance systems and other types of social safety nets. The ACTION study is a longitudinal cohort study of 10,000 hospital patients with a first time diagnosis of cancer. It aims to assess the impact of cancer on the economic circumstances of patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
1
28
0
1
Order By: Relevance
“…As such, this study was not prespecified in the published protocol. 17 The rationale for assessing 3-month outcomes was our specific interest in the economic burden incurred in the acute phase of the disease as a result of surgery. This study was approved by the University of Sydney's Human Research Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, this study was not prespecified in the published protocol. 17 The rationale for assessing 3-month outcomes was our specific interest in the economic burden incurred in the acute phase of the disease as a result of surgery. This study was approved by the University of Sydney's Human Research Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…The ACTION (Asean CosTs In ONcology) study is a prospective, longitudinal study examining the economic impact of cancer on households in 8 countries in ASEAN. 17 Patients diagnosed with a first time cancer (aged $ 18 years) were recruited consecutively from 47 sites including public and private hospitals and cancer centers. Participants completed interviews at baseline, and 3 and 12 months after diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…The ACTION study was a longitudinal study of 9513 newly diagnosed cancer patients in eight LMICs in Southeast Asia, set up to prospectively assess the impact of cancer on households’ economic wellbeing and health [9]. Results of the study reported thus far have demonstrated that families living in Southeast Asia struggled to manage the costs associated with cancer care; over half the households faced catastrophic out-of-pocket payments (defined as spending more than 30% of household income for cancer-related costs) in the year after diagnosis [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of new, expensive antineoplastics and therapeutic techniques increases the cost of treatment (Jönsson et al, 2007;Meropol et al, 2007;Yabroff et al, 2007;Kimman et al, 2012). Cancer accounts for 13-17% of all disease burden and 4-7% of total global medical expenditure (Jönsson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%